JQuery Mobile cookbook. : over 80 recipes with examples and practical tips to help you quickly learn and develop cross-platform applications with jQuery Mobile /: over 80 recipes with examples and practical tips to help you quickly learn and develop cross-platform applications with jQuery Mobile. (2012) - Jain, Chetan K
No abstract available